Lessons learned from redesigning public health medicines supply chain model in Uttar Pradesh, India - Namasivayam, Vasanthakumar; Purwar, Manuj; Jain, Sushant; Halli, Shivalingappa; Kumar, Jagdeesh; Gothalwal, Vikas; Becker, Marissa; Blanchard, James; Boerma, Ties; Prakash, Ravi (Frontiers in Public Health, 2025)
Uttar Pradesh (UP), the most populous state of India with 238 million people, has over 30,000 public health facilities. Ensuring the continuous availability of essential medicines across these facilities is a significant challenge. An audit conducted in 2017 indicated large gaps in the availability of essential medicines in public health facilities. This study describes the lessons from Tamil Nadu’s Medical Supplies Corporation (TNMSC) that were adapted to inform the redesign of the medicines supply chain model and processes of Uttar Pradesh’s Medical Supplies Corporation (UPMSC). We identified seven essential pillars for a successful public health supply chain system through a desk review and learnings from TNMSC. These included a stable list of essential medicines, warehouses, centralized procurement, a passbook system, quality control, centralized payment, and digital e-tracking to enable real-time inventory and procurement decisions. The system design established a clear responsibility matrix: UPMSC is responsible for ensuring the availability of all essential medicines in the district warehouses at all times. The facility in-charge is responsible for ensuring the availability of the required drugs at the facility. The facilities are notionally allotted a budget and have complete freedom to pickup medicines from the warehouse, as long as they remain within the budget available. Under these seven essential pillars, several key processes were undertaken to improve vendor participation, reduce vendor dependency, synchronize tenders for all essential drugs, and establish rosters for facilities to pick up drugs from the warehouse. These efforts led to an improvement in the availability of essential medicines from 40% to 100%, with an average of 275 medicines out of 287 medicines available per warehouse. Supply orders increased from 58 million to 112 million, and facilities consumption value increased from 38 million to 90 million by April 2024. However, challenges such as last-mile delivery and prompt payment to vendors remain. This paper underscores the importance of system design in the public health supply chain and may be useful for other Indian states and low- and lower-middle-income countries (LMICs) with a similar context.